Politics of Leadership: Exploration of Transparency in Constructing Public Trust during the Covid-19 Pandemic in Nganjuk - Fitriyatuz Zahro; Erna Setijaningrum; Eko Supeno (LEGAL BRIEF, 2022)
This research aims to measure the level of transparency that must be done by local governments to raise public trust in society. It is interesting to see the perspectives of society and government. What kind of transparency that the government thinks can be published and what kind of transparency the society wants. Using a descriptive approach involving interviews, observation, and review of relevant documents, this research was conducted in Nganjuk. The result of this research was found that transparency contributed greatly to public trust. The transparency that is meant by the public is written accountability for every step taken by the government and always involves the community, especially the leaders of NGOs (Non- Government Organizations). Meanwhile, according to the government, in every step taken by the government, several things should not be consumed by the public to avoid misunderstanding. The government considers that each policy step is based on several conditions and situations. If the public reads the data with the naked eye, it will lead to many problems in the future. Transparency of data for the government is related to the publication of results and accountability at the end of the term of office. In conclusion, the understanding of transparency according to both parties is different. Therefore, the government has to inform the harmony of understanding about transparency. So that no miscommunication leads the government's actions to be considered incorrect by society.